EKSISTENSI LAGU “OJO DIBANDINGKE” DALAM PENDIDIKAN ANAK USIA DINI - , Nurafia Hamka; Musyarrafah; Syarifah Halifah (Awladuna: Jurnal Pendidikan Islam Anak Usia Dini, 2023)
The existence of the Ojo Dibandingke song in Early Childhood Education. The purpose of this study is to find out how the influence of the Ojo Dibandingke song on children aged 4 and 5 years. This Ojo Dibandingke song affects the activities that children do because they often listen to it on YouTube and Tiktok media. This study uses qualitative research techniques with a case study approach. The subjects of this study were children aged 4 and 5 years. This research was conducted at the residence of MD and AA. Research shows that MD and AA prefer to listen to Ojo's songs compared to via YouTube and TikTok.